The Effect of Using Single Retention on Papermaking Process to Improve Product Quality and Reduce Costs: Case study Brown Paper Manufacturing - Aldy Pradana; Ni Njoman Manik; Amelia Rahmatika; Erwin (Universitas Medan Area, 2025)
Many objects around us use paper-based materials. Recycle fiber is an alternative raw material with great potential to meet fiber needs and overcome environmental problems. Paper with virgin pulp raw materials has a higher production cost than paper with recycled fiber raw materials. Apart from fiber raw materials, the chemicals used also cause high production process costs. Currently, the industry uses a double retention system for 63,022.5 per month; this cost comes from using more chemicals. This study aims to determine the effect of the use of single retention on machine run ability and the quality of paper produced and to find out how much production cost savings from the use of single retention. In this study, brown paper was made using CPAM chemicals as retention materials and silica as comparison retention materials with doses of 0.25kg/ton, 0.5kg/ton, 0.75kg/ton, and 1kg/ton, respectively. Then, wet-end properties testing was carried out, which included drainage and FPR. Furthermore, dry-end properties testing, which included internal bonding, concord, ring crush, and tensile testing, was carried out on a laboratory scale. The results showed that using a maximum dose of cpam of 0.25kg/ton got better results. In using cpam above 0.25 kg/ton, quality degradation results are obtained, but the drainage produced continues to increase as the dose increases; this is influenced by the amount of floc formed in the stock, thus affecting the run ability of the machine. After research and calculations with the application of single retention in the brown paper manufacturing process, considerable cost savings were obtained, and quality can be maintained using strength agents.